Avaibility and extraction of natural heritage in wetland areas: case studies at taman alam and kampung kuantan, kuala selangor, selangor - Harun, Nor Zalina (s.n, 2012)
This research focuses on the concept of natural heritage and briefly describes the special attributes of natural heritage in Kuala Selangor. The research represents a beginning step toward a compilation of information of preservation of natural heritage process. It is limited in scope, taxonomically to the flora and fauna, and geographically to the two natural areas in Kuala Selangor: Kuala Selangor Nature Park and Kampung Kuantan. Kuala Selangor Nature Park (KNSP) or locally known as Taman Alam was developed due to the concern by Malaysian Nature Society particularly on the plight of migratory birds in Kuala Selangor after discovering the lost of many of their transit rest areas due to development and Kampung Kuantan is the best-known place for firefly colony in Malaysia. They act as a sanctuary for many mammals and migratory bird and the endangered fire flies.